(untitled) (Research, Society and Development, 2022)
The History of Professional and Technological Education (PTE) in Amapá has gaps in terms of the adequacy of the course curricula to the guiding norms for creating and developing these curricula. Therefore, as a research problem, it was investigated: what are the historical bases of the PTE legislation, offered in Amapá, since the creation of the Federal Territory? As an objective, we sought to understand the conceptual bases that ran through the PTE curriculum to contribute to the study of professional education in Amapá. Methodologically, bibliographic and documentary research was used to outline the educational norms of each period, the history of Amapá’s professional technical schools, and their official curricula, as well as to collect data on how the legislation was put into practice in the classroom. From this research, it is expected to contribute to broadening the debate on the curriculum of professional education in Amapá, its tools, conceptual bases, mistakes and successes of each historical phase, and relevant legislation for the construction of a curricular profile of professional education in Amapá more suited to local needs and requirements, with their peculiarities and adversities.